A review of geometric sensitivities in laser metal 3D printing. Issue 2 (2nd April 2020) - Chahal, Vedant; Taylor, Robert M.
ABSTRACT: This paper examines the relationships in laser metal additive manufacturing between part geometry and as-built part quality, including residual stresses, deformations, process induced porosity, surface roughness, and microstructural variations. A comprehensive review of these defects and their relationships with the geometric features are provided along with a brief discussion of the involved physical phenomena. Specific design guidelines are also provided to facilitate a more robust design for structural applications. This review further highlights the need to pursue the development of design methodologies, including automated topology, shape, and sizing optimisation methods, that help derives an optimal design tailored for these process-induced quality considerations in laser metal additive manufacturing that affect structural performance.